Nutritional Approaches for Prevantion and Treatment of Metabolic Syndrome in Adults - Ebrahimof, Samira; Mirmiran, Parvin (Archives of Advances in Biosciences, 2013)
Metabolic syndrome, a clustering of components that reflect overnutrition, sedentary lifestyles, and excess adiposity, has become a major health problem worldwide. The increase in its prevalence could be the result of the increase in obesity and insulin resistance. It is suggested that modification of lifestyle including increasing exercise and improving dietary habits is an effective approach for management of the metabolic syndrome. No single diet is recommended for patients with metabolic syndrome. This paper will review the data and make an evidence-based recommendation for the optimal dietary patterns for reducing cardiometabolic risk.